Performa Ayam Kampung Periode Starter Pada Peternakan Rakyat yang Diberi Ampas Sagu Dalam Ransum - Rajab Rajab; Tabita Naomi Ralahalu (Universitas Islam Kadiri, 2021)
Sagoo by product can be used with purpose of poultry alternative feed pakan, such as fed energy source of Kampong chicken, caused by the content of energy metabolism of sago by product reach 2340 Kcal/kg, crude protein 3.40%, and crude fibre 11.61%. This research aims was to know the performance of Kampong chicken on starter period given by feed with contain sago by product, as representing form of application of exploiting of local feed source especially waste of sago processing which was a lot of there in Maluku Province. The Research study was conducted in rural ranch of Kampong chicken, and take place during two months. This research used the experimental method to compare the performa of Kampong chicken on starter period (0- 4 week of age) which rearing by local breeder. The results showed the performance of Kampong chicken given by feed with contain sagoo by product were 27.11 – 32.85 g/tail/day, 10.19 – 13.49 g/tail/day, 2.43 – 2.66, and 0 % respectively for feed consumtion, average daily gain, feed convertion rate, and mortality rate. It can be concluded than sagoo by product can be used as Kampong chicken feed on starter period.